'We Have Lost Our Lives Already': Loss and Coping among Sri Lankan Women. Issue 10 (25th November 2020) - Banford Witting, Alyssa; Hughes Barrow, Betsy; Lambert, Jessica; Whiting, Jason; Hartshorn, Rachel; Marks, Loren; Wickrama, Thulitha; Thanigaseelan, Seevaguru
ABSTRACT: Widowed women affected by the Sri Lankan war conflict (1983–2009) and the 2004 tsunami face challenges, many of them in consequence of losses incurred in mass trauma. These women also display internal and communal resilience to loss. Three focus group discussions were conducted and analyzed with 21 Tamil, widowed women across three communities affected by tsunami and/or war exposure. Using grounded theory methods, the researchers addressed questions about the experience of widowhood in a postwar, post-disaster context and related losses. A theoretical model was developed, suggesting a contextually specific loss process wherein that participants experienced significant losses directly related to the war and tsunami and that they experienced losses that were contextually related to the war and tsunami, meaning losses that followed those events or were connected to or exacerbated by them. In response to these losses, participants described focusing attention away from their own lives and adopting a sacrificial orientation to the future and their children's lives, engaging in religious practices, and receiving support from others, including other widowed women.